No water to waste - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Proper management of irrigation is key to sound water management. Various tools can help to assess current situations and design future scenarios in water use in irrigation, and also facilitate an informed dialogue for preventing conflicts over...